Determinants of consumer safety practices in the motor vehicle repair and service industries - Isa, Nurul Syamimi; Abu Bakar, Elistina; Osman, Syuhaily (Malaysian Consumer and Family Economics Association, 2015)
The increase in the number of registered vehicles and the number of licensed drivers over the years has resulted in high demand for the motor vehicle repair and service industry in Malaysia. The objective of this study is to examine the determinant factors of consumers’ safety practices in this industry. A total of five hundred respondents in the Klang Valley were chosen through multistage random sampling. Multiple regressions analysis is used to identify the factors that contributed to the consumer safety practices. The factors include demographic background of gender and education level, worry about accident risk and safety priority. The results show that safety priority is the strongest predictive factor in safety practices. Thus, this study suggests that for policy implication where the respective bodies should inculcate safety practices to all consumers irrespective of their gender and education through the formal or informal community programme. These findings will support the suggestion to consumer movements and the government in order to educate consumers to be responsible for putting safety as a priority in choosing the better workshop for repair and services their motor vehicle in the future. Thus, this study suggests that for policy implication where the respective bodies should inculcate safety practices to all consumers irrespective of their gender and education through the formal or informal community programme. These findings will support the suggestion to consumer movements and the government in order to educate consumers to be responsible for putting safety as a priority in choosing the better workshop for repair and services their motor vehicle in the future.